EVALUASI KEBIJAKAN PENGELOLAAN LINGKUNGAN PERTAMBANGAN DI PULAU OBI PROVINSI MALUKU UTARA - Zulkifli Zam Zam; I Made Putrawan (Jurnal Ilmiah Pendidikan Lingkungan dan Pembangunan, 2020)
Nickel mining activities in Obi Island, North Maluku Province use open-pit techniques, causing environmental problems. The purpose of this study was to evaluate the environmental conditions of the mining area and evaluate the obligations of the government of South Halmahera Regency in preparing and implementing environmental management instruments in accordance with UU No.32/2009. This research is a policy research to evaluate mining activities, using the Haas & Springer evaluation model. The results showed that mining activities in Obi Island, North Maluku Province caused a decrease in the quality of the environment, due to the Government of South Halmahera Regency which was not consistent in protecting and managing the environment, especially in the mining area, this can be seen from the absence of RTRW / RPMJD KLHS Documents, implementation of the UKL / UPL AMDAL that is not yet optimal, and there is no standard for B3 waste management and B3 waste dumping to the environmental media. Thus, the local Regency Government has not been able to implement environmental law policies properly, effectively and efficiently.